Treatment of Early Stage Tonsil Cancer in the Age of Human Papillomavirus–Associated Malignancies. (July 2021) - Patel, Evan J.; Zhu, Angela W.; Oliver, Jamie R.; Cornwell, MacIntosh; Jacobson, Adam S.; Hu, Kenneth S.; Tam, Moses; Vaezi, Alec; Morris, Luc G. T.; Givi, Babak
Objective: To investigate the patterns of care and outcomes of treatment of early stage tonsil cancers, controlling for human papillomavirus (HPV) status. Study Design: Historical cohort study. Setting: National Cancer Database (NCDB). Methods: Review of the NCDB between 2010 and 2017 for all T1-2N0M0 tonsillar squamous cell carcinoma (SCC). Demographics, clinical characteristics, HPV status, treatment regimens, and survival were analyzed. Results: A total of 4720 patients were identified with early stage SCC of the tonsil. Most were tested for HPV (2759 [58.5%]). Among tested patients, 1758 (63.7%) were positive for HPV and 1001 (36.3%) were negative for HPV. HPV-positive patients had higher 3-year survival compared to HPV-negative patients (93.2% vs 77.8%, P < .001). Among HPV-positive patients, there was no significant difference in survival between treatment cohorts. However, in the HPV-negative cohort, 3-year survival was higher in both bimodality surgical-based settings (tonsillectomy + neck dissection + radiotherapy, 86.0% vs chemoradiotherapy, 69.6%, P = .01) and for all surgical-based treatments when compared to nonsurgical management (84.6% vs 69.3%, P < .001). This difference was maintained in multivariable regression controlling for age, sex, comorbidities, clinical T stage, and treatments. In a subpopulation of HPV-negative patients propensity score matched by all factors significant in multivariable analysis, 3-year survival remained higher in the surgically treated group compared to the nonsurgically treated cohort (84.9% vs 67.1%, P < .001). Conclusions: Surgical- or radiation-based treatment resulted in similar survival in early stage HPV-positive tonsil cancer. Surgical-based treatments were associated with longer survival in HPV-negative cancers. These findings should be further investigated in a randomized prospective trial.